Is Pedometer-Determined Physical Activity Decreasing in Czech Adults? Findings from 2008 to 2013 - Pelclová, Jana; Frömel, Karel; Řepka, Emil; Bláha, Ladislav; Suchomel, Aleš; Fojtík, Igor; Feltlová, Dana; Valach, Petr; Horák, Svatopluk; Nykodým, Jiří; Vorlíček, Michal (International journal of environmental research and public health, 2016)
Objective measured trend data are important for public health practice. However, these data are rare for an adult population. Therefore, the aim of this study was to describe time trends in pedometer-determined physical activity of Czech adults (25-65 years) from 2008 to 2013. Participants were Czech national citizens whose physical activity was assessed objectively using a Yamax Digiwalker SW-700 pedometer (Yamax Corporation, Tokyo, Japan) for seven consecutive days in the period 2008 to 2013. The final sample was 4647 Czech adults [M age 41.4 ± 10 years; M body mass index (BMI) 25.1 ± 3.7 kg/m²]. The results showed that men took more steps/day (M (Mean) = 10,014; 95% CI (Confidence Interval) = 9864-10,164) than women (M = 9448; 95% CI = 9322-9673) in all age and BMI groups. Mean steps/day declined from 2008 to 2013 by 852 steps/day in men and 1491 steps/day in women. In the whole sample, the proportion of participants who had a sedentary lifestyle (<5000 steps/day) increased by 5.8%; the proportion taking ≥10,000 steps/day decreased by 15.8%. In 2013, men and women were 2.67 and 2.05 times, respectively, more likely to have a physically inactive lifestyle (<7500 steps/day) than in 2008. Conversely, in 2008, men and women were 1.68 and 2.46 times, respectively, less likely to have very active lifestyle (>12,500 steps/day). In conclusion, this study suggests that there has been a substantial reduction in physical activity in Czech adults over time.
Keywords: aktigrafie; dospělí; Sedentary Behavior; Female; Adult; ženské pohlaví; sedavý životní styl; step-based categories; lidé; cvičení; inactive lifestyle; very active lifestyle; Actigraphy; Male; Aged; Czech Republic; step counts; Česká republika; lidé středního věku; senioři; mužské pohlaví; time trends; Exercise; Middle Aged; Humans